The INFLUENCE OF INSTAGRAM SOCIAL MEDIA, PEER GROUPS, AND LIFESTYLE ON CONSUMPTION BEHAVIOR ON STATE STATE HIGH SCHOOL STUDENTS IN MAKASSAR CITY - Rusdi Raprayogha; Muslimin Kara; Nahda Dahlan (Jurnal Asy-Syarikah: Jurnal Lembaga Keuangan, Ekonomi dan Bisnis Islam, 2021)
This study aims to examine the influence of social media Instagram, peer groups and lifestyle on consumptive behavior in State University students in Makassar City. The variables used in this study are Instagram social media, peer groups and lifestyle as independent variables, and consumptive behavior. as the dependent variable. This research is a quantitative research. The data sources in this study are primary data and secondary data, where the data collection method uses a questionnaire method which is distributed to all students in State Universities in Makassar City. The number of samples used is 100 respondents. primary data using Statistical Packege For Social Science (SPSS) version 22 analysis technique. The results of this study indicate that Instagram social media has a positive and significant effect on consumptive behavior. Peer groups have a positive and significant effect on consumptive behavior. Lifestyle has a positive and significant effect on consumptive behavior. As well as social media Instagram, peer groups and lifestyle simultaneously have a positive and significant effect on consumptive behavior.